2022
DOI: 10.5194/amt-15-365-2022
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial neural networks to predict riming from Doppler cloud radar observations

Abstract: Abstract. Riming, i.e., the accretion and freezing of supercooled liquid water (SLW) on ice particles in mixed-phase clouds, is an important pathway for precipitation formation. Detecting and quantifying riming using ground-based cloud radar observations is of great interest; however, approaches based on measurements of the mean Doppler velocity (MDV) are unfeasible in convective and orographically influenced cloud systems. Here, we show how artificial neural networks (ANNs) can be used to predict riming using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Machine learning techniques can also be used for classifying hydrometeor types. Neural networks in particular have been used for particle characterization (Liu & Chandrasekar, 2000), or detection of supercooled liquid (Luke et al, 2010) and detection of riming (Vogl et al, 2022) in mixed-phase clouds. Roberto et al (2017) used a Support Vector Machine (SVM) to classify particles in dual-polarization radar observations, which was trained and evaluated with classifications from a fuzzy logic algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning techniques can also be used for classifying hydrometeor types. Neural networks in particular have been used for particle characterization (Liu & Chandrasekar, 2000), or detection of supercooled liquid (Luke et al, 2010) and detection of riming (Vogl et al, 2022) in mixed-phase clouds. Roberto et al (2017) used a Support Vector Machine (SVM) to classify particles in dual-polarization radar observations, which was trained and evaluated with classifications from a fuzzy logic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques can also be used for classifying hydrometeor types. Neural networks in particular have been used for particle characterization (Liu & Chandrasekar, 2000), or detection of supercooled liquid (Luke et al., 2010) and detection of riming (Vogl et al., 2022) in mixed‐phase clouds. Roberto et al.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the typical degree of riming for individual modes of frozen precipitation allows a high-resolution analysis of the principal particle growth mechanisms in precipitating clouds above the melting layer. Future efforts could also include testing another recently introduced approach for retrieving the rime mass fraction from radar Doppler spectra that is less impacted by vertical air movements than the method employed in this study (Vogl et al, 2022). These riming retrievals can then be combined with scanning polarimetric radar measurements or atmospheric wind and temperature fields derived from atmospheric models to provide a more complete picture of precipitation microphysics and atmospheric thermodynamics (Oue et al, 2018;Trömel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These applications are particularly powerful due to their ability to perform part of the data pre-processing themselves. Vogl et al (2022) showed that ANNs can be used to predict riming using ground-based zenith-pointing cloud radar variables radar reflectivity, spectrum width, and skewness. An earlier approach from Luke et al (2010) transfers the features of Doppler spectra into particle backscatter and volume depolarization of a high-spectral-resolution lidar (HSRL) using a multi-layer perceptron model and was further validated by Kalesse-Los et al (2022) by applying the pretrained machine learning model to data from the Analysis of the Composition of Clouds with Extended Polarization Techniques (ACCEPT) campaign (Myagkov et al, 2016a;Myagkov et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%